GUIDELINES FOR DEVELOPING THE PARTICIPATION OF SCHOOL BOARDS AND SCHOOL ADMINISTRATIONS IN THE NEXT NORMAL IN THE EDUCATION SANDBOX OF TRAT PROVINCE - Buakeaw, Kitipan; Warabamrungkul , Theerangkoon; Nilkote, Reongwit (Journal of MCU Nakhondhat, 2024)
The purposes of this research are to 1) Study the development of participation of school boards in the new normal administration, 2) Study the level of development of participation of school board members in the new normal in the new normal administration, and 3) Present guidelines for developing the participation of school boards in the new normal administration; Education Sandbox, Trat Province. It is a combined method research. The quantitative tool is a questionnaire. The sample size was 260 people. Proportional Stratified Random Sampling was used, using the size of the educational institution as the sampling stratum. Data were analyzed by means, standard deviations, t-tests, and one-way analysis of variance. Qualitative research tools are structured questionnaires. There were 12 key informants. They were selected purposively with criteria of being school administrators, teachers with 5 years of experience, and willing to provide information. Content analysis and examined using triangulation techniques. The results showed that participatory development consisted of analysis of potential capital, formulation of innovation as needed, innovation development, determination of the effectiveness of educational innovation, contextual experimentation, evaluation, and amplification, The comparative results on participation development. They are classified by district as a whole and by side to a large extent. In descending order are personnel management, general administration, academic administration, and budget management. There was a statistically significant difference at the level. 0.5. And Approaches to engagement development include creating engagement spaces, holistic support, policies and strategic plans, developing professional skills, and creating transparency.